2013
DOI: 10.1103/physreva.87.013425
|View full text |Cite
|
Sign up to set email alerts
|

Stability and dynamics of ion rings in linear multipole traps

Abstract: Trapped singly-charged ions can crystallize as a result of laser cooling. The emerging structure depends on the number of particles and on the geometry of the trapping potential. In linear multipole radiofrequency traps, the geometry of the radial potential can lead to the formation of single-ring structures. We analyse the conditions and stability of single rings as a function of the number of poles. The rings form tubes for a large number of ions and sufficiently small trap aspect ratios. In these structures… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
(75 reference statements)
0
22
0
Order By: Relevance
“…crystals in thermodynamic limit or with periodic boundary conditions. Such homogeneous systems could be realized in the laboratory in ring traps [36,37] and octupole traps [38][39][40].…”
Section: Ion Crystals and Ginzburg-landau Modelmentioning
confidence: 99%
“…crystals in thermodynamic limit or with periodic boundary conditions. Such homogeneous systems could be realized in the laboratory in ring traps [36,37] and octupole traps [38][39][40].…”
Section: Ion Crystals and Ginzburg-landau Modelmentioning
confidence: 99%
“…We have shown that, for charged particles confined on a ID closed helix, a linear to zigzag-like bifurcation occurs when increasing the radius of the helix at commensurate fillings. Similar transitions are known for linear Wigner crystals under harmonic [15][16][17][18][19][20] or octupole trapping [21,22], where they are driven by the increment of dimen sionality from one dimension to three dimensions controlled by the transverse trapping potential. In our case, however, the single-particle configuration space remains always strictly ID, which manifests itself in the way in which the critical value ra is reached.…”
Section: Introductionmentioning
confidence: 77%
“…1(c). It is found provided the number of particles is even, while for odd N the structure exhibits topological defects [33]. expected square-root behavior predicted by the Landau theory for a second-order phase transition [12,20].…”
Section: Minimal-energy Configurationsmentioning
confidence: 88%